Effectiveness of Musical Training on Reading Comprehension in Elementary School Children. Is There an Associative Cognitive Benefit? - Sofologi, Maria; Papatzikis, Efthymios; Kougioumtzis, Georgios; Kosmidou, Elina; Klitsioti, Asimenia; Droutme, Andreani; Sourbi, Aggeliki-Anna; Chrisostomou, Dimitra; Efstratopoulou, Maria (Frontiers in Education, 2022)
The current study investigated the impact of instrumental music training in reading comprehension and executive function in elementary school children in Greece. A series of studies suggested the possibility of a cognitive advantage from instrumental music training. For the purpose of the present study 80 elementary school children were evaluated. The experimental group consisted of 40 students of 5th grade with at least 5 years of music training and the control group consisted of 40 children who did not have any music training. The two groups were examined in working memory measurements, executive functions and reading comprehension tests. Children with instrumental music training showed higher performances in reading comprehension test and in all cognitive measurements reflecting a possible cognitive advantage in comparison with participants without music training. The present results attempt to shed light on the possible link of instrumental music training on cognitive abilities and reading comprehension.